NORTHERN SEA ROUTE - RUSSIA AND CHINA: COMPETITION OR PARTNERSHIP - Mekhdiev, Elnur; Zakharevich, Ekaterina; Mammadova, Parvana; Jumayev, Farrukh (Editorial Internacional ERUDITUS, S.L, 2021)
The Northern Sea Route (NSR) is one of Russia’s and Eurasia’s key arteries as a whole, connecting Asia and Europe. Being the shortest and the most difficult route for navigation, the NSR is of great interest for exploring its development potential, especially taking into account the fact that a new player is appearing in the Arctic arena: we speak about China. Within the article, the authors raise the question of what kind of future the NSR will have in the context of cooperation or competition between the Russian Federation and China in the development and in the NSR capacities development. Within the research a quantitative analysis of the goods’ and ships’ traffic by the NSR is carried out; the authors also make forecasts about its development for the period up to 2025. The authors come to the conclusion that traffic along the NSR is growing, but slowly; the Chinese presence is currently insignificant, that’s why the Russian Federation will have to develop the NSR without the active PRC’s support. Competition on the way will be delayed to a higher level of NSR infrastructure’s development.